PELANGGARAN PENGGUNAAN GAMBAR “LASKAR CINTA” PADA DESAIN PRODUK KAUS BERDASARKAN UNDANG-UNDANG NOMOR 31 TAHUN 2000: Unauthorized Used Of The “Laskar Cinta” Image On T-Shirt Designgs According To Law Number 31 Of 2000 - Laksamana Cristian; Rakhmita Desmayanti (Reformasi Hukum Trisakti, 2024)
A A design is achieved through extensive time, effort, and thought, resulting in a design that sets a product apart from others. For example, the "Laskar Cinta" image on Dewa 19 T-shirts is different from other T-shirts. However, there have been violations of the "Laskar Cinta" image design, such as piracy and plagiarism. This article discusses the use of the "Laskar Cinta" image as a T-shirt product design. The problem addressed is how Law Number 31 of 2000 protects such image designs and whether unauthorized use of the "Laskar Cinta" image can be subject to sanctions as regulated in Articles 46 and 54. The research employs normative and descriptive methods, analyzing secondary data supported by primary data qualitatively. Conclusions are drawn using deductive logic. The results show that the requirement for novelty is absolute; novelty means the design must not have been disclosed to the public before registration with the Directorate General of Intellectual Property, as stipulated in Article 2. Protection is only granted to those who have registered and received a certificate for their industrial design.